Neurologic Localizations - John Pearson; Mark Rich; Dean Parmelee (Association of American Medical Colleges, 2010)
Abstract This module uses two clinical scenarios (brainstem infarct; multiple extra-dural abscesses) to help students learn how to apply basic neuroscience content knowledge to lesion localization. The module begins with students arriving having read necessary advanced-preparation readings. Students then take a readiness assurance test, a measure of how well students have mastered fundamental content knowledge, such as the structure and function of neural pathways and cranial nerves. A series of group application exercises (GAEs) then requires students to apply this knowledge to solve clinical problems in neurology, namely, lesion localizations. In these exercises, teams are required to submit written answers that the faculty then sorts into five choice-groups (based on similarity of content). The choice-groups are posted for all teams to read and discuss. Each team then selects the one group of written responses they feel best answers the original question. Voting and intra-team discussion follow. A period of 1.5 hours is recommended for the GAE to enable students to write descriptions of the lesion location, read descriptions posted by other teams, and choose the best localization from among the groups of written descriptions. Large post-it note pads with markers and up-front board space to post and view descriptions are needed for these sessions. This module effectively helps students think and respond at a level of creativity beyond that typically required of multiple-choice questions (MCQs), yet stays within the beneficial structural framework similar to a team-based learning format. In addition to using traditional MCQs, this module introduces a student-initiated MCQ exercise in which written answers submitted by the teams are used to formulate the multiple-choice answers from which teams select a final answer to the original question.